Innovations, high-tech trade and industrial development: Theory, evidence and policy - Lakhwinder Singh (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2006)
Innovations spur science-based trade and industrial development in a fast changing pace of globalization. Knowledge accumulation and diffusion have been increasingly recognised as fundamental factors that play an important role in long-run economic growth. This paper focuses on the long-term innovation strategy of industrial and technological development in developing countries. Growth theory, empirical evidence and several indicators of innovation have been pressed into service to draw important lessons from historical experience of the developed and newly industrializing countries for the industrial development of the developing economies. Technology development and public technology policy experience of the East Asian countries have been examined to reinvent the role of public technology policy that can be adopted to develop national innovation system to nurture and build innovative capabilities in the developing economies in the dynamic global economy. – innovations ; growth ; high-technology ; Asia ; government policy
Keywords: F2; O1; O3; 330; Innovationspolitik; Hochtechnologiesektor; Asien